Traditions of Hadith Interpretation in Determining Patterns of Istinbāṭ: A Comparative Study of Medina and Kufa in the Early Islamic Period (1st–2nd Century AH) - Akhnaf, Muhammad; Amrullah, Abdul Karim; Sangidun; M. Hamsa Fauriz (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study explores the differences in the tradition of hadith interpretation in the development of Islamic jurisprudence in two early intellectual centers of Islam: Madinah and Kufah during the 1st–2nd centuries AH. These two regions exhibited distinct methodological approaches in understanding and applying hadith as a source of Islamic law. Madinah is characterized by a literal and practice-based approach grounded in ‘amal ahl al-Madīnah, emphasizing the continuity of the Companions’ traditions and social stability as the foundation of legal legitimacy. In contrast, Kufah developed a more rational and selective interpretative model, shaped by complex socio-political conditions and caution toward hadith transmission influenced by various ideological groups. This research employs a qualitative method with historical and comparative approaches to trace the social contexts, transmission networks, and characteristics of legal reasoning (istinbāṭ) methodologies adopted by scholars from both cities. The findings reveal that these divergent approaches not only influenced perspectives on hadith but also shaped distinctive regional schools of jurisprudence. Thus, this study offers a significant contribution to understanding the early dynamics of Islamic legal formation and the methodological roots of later madhhab differences.